Analysis of Arabic Language Learning Difficulties Among Students in the Qawaid Al-Lughah Al-Arabiyyah Materials - Hastang, Hastang; R., Ahmad (Fakultas Tarbiyah Institut Agama Islam Negeri (IAIN) Bone, 2023)
Mastery of qawaid al-lughah al-arabiyyah material is fundamental for students in the Arabic language education study program as it lays the groundwork for mastering the four essential language skills: istima', kalam, qira'ah, and kitabah. Despite its significance, students encounter difficulties in comprehending this material. This qualitative descriptive study conducted at IAIN Bone involves eight students and two lecturers from the Arabic education study program, employing in-depth interviews, observations, and documentation for data collection. The thematic analysis reveals three main findings: 1) Learning difficulties are categorized into nahwu and sharaf, encompassing challenges in grasping new terms, creating examples, applying rules, analyzing sentence elements, and understanding wazan and shigat. 2) Factors contributing to these difficulties include inadequate face-to-face learning schedules, infrequent lesson repetition, limited self-practice, excessive reliance on online learning, a less supportive environment, and insufficient learning facilities. 3) To overcome these challenges, students take individual initiatives, including self-motivation, completing learning activities, forming communication and study groups, actively participating in the learning process, and enrolling in training/courses. Addressing these challenges can enhance Arabic language education, enabling students to achieve proficiency in qawaid al-lughah al-arabiyyah and the four language skills.Keywords: Arabic learning, Learning difficulties, Nahwu, Sharaf, Qawaid al-lughah al-arabiyyahÂ Â